SOMEONE ASKED 👇
Y = 3 ( x + 5 ) ( x – 2 ) how do i solve it?
HERE THE ANSWERS 👇

There is a process called FOIL, which is used to multiply out factored equations. What you do is you multiply the first two terms, then the outer two, then the interior two, and finally the last two.
Your problem for example 3(x + 5)(x – 2) can be foiled out to 3(x^2 – 2x + 5x – 10). If you combine like terms you are left with 3(x^2 + 3x – 10). Now use the distributive property to multiply the 3 to everything in the parentheses to get 3x^2 + 9x – 30.

FOIL (x+5)(x2)
=x^2 2x + 5x – 10
=x^2 + 3x – 10
distributive law
3(x^2+3x 10)
=3x^2 + 9x – 30

y=3(x+5)(x2)
y=3(x*2+3x10)
y=3x^2+9x30 good luck

y = 3 ( x + 5 ) ( x – 2 )
(a+b)(c+d) = ac + ad + bc + bd
y = (3x+15) (x2) = 3x.x + 3x.(2) + 15.x + 15(2)
= 3x² + (6x) + 15x + (30)
= 3x² – 6x + 15x – 30
= 3x² + 9x 10
Leave a Reply